Peran Strategis Guru Pendidikan Kewarganegaraan dalam Pembentukan Karakter Disiplin Peserta Didik di Era Digital - Annisa Nurwahidah Larasati; Syamzaimar (Ruang Publikasi Ilmiah, 2026)
This study discusses the strategic role of Civic Education teachers in shaping students’ disciplinary character. Discipline is one of the important characters that must be developed in the educational process because it influences students’ attitudes and behavior in everyday life. The purpose of this study is to analyze the role of Civic Education teachers in fostering discipline through exemplary behavior, habituation, supervision, and educational sanctions. This research used a qualitative descriptive method with a literature study approach by examining various scientific journals, books, and relevant references related to character education and discipline. The results showed that Civic Education teachers have a significant role in shaping disciplinary character through role modeling, the application of school rules, motivation, and continuous guidance. The implementation of discipline character education can create responsible, orderly, and law-abiding students. Therefore, collaboration between teachers, schools, parents, and the community is needed to strengthen students’ disciplinary character.